In silico characterization of QTL regions associated with drought tolerance traits in rice (Oryza sativa L.) - Sinha, Sweta; Kotasthane, A. S.; Verulkar, S. B. (The Indian Journal of Genetics and Plant Breeding, 2017)
An attempt was made to carry out in silico characterizationof 14 putative QTL regions identified on chromosomes 1,2, 4, 5, 6 and 8 associated with drought tolerance. A total of354 BAC/PAC clones were detected in the underlyingregions of putative QTLs mapped. These BAC/PAC clonenucleotide sequences were used for mining SSRs and primerdesigning. The tri-nucleotide motif was the most abundantclass which was followed by tetra, di, penta and hexanucleotide repeats. A total of 1849 class I SSR markers weredesigned from QTL regions. The underlying regions ofputative QTL displayed different functional categories ofdrought tolerance genes, transcription factors (45.65 %),protein kinases (33.94 %), stress proteins (10.11 %),phytohormones (9.75 %) and aquaporins (0.72 %). Themassively parallel signature sequence (MPSS) analysis ofcandidate genes showed higher expression fortranscription factor having WRKY and zinc finger superfamily (LOC_Os02g08440) in stem, immature panicle,developing seeds, mature leaves, mature roots, merismatictissues, cold, drought and salt stressed young rootstranscript tissue library. The functional validation identifiedputative genes based on MPSS signatures will facilitate tounravel the complexity of drought tolerance at molecularlevel and further will accelerate the genetic improvement ofdrought tolerance in rice.